Implementation of Academic Supervision and Teacher Performance Assessment - Halmaida Halmaida; Yusrizal Yusrizal; Niswanto Niswanto (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study was to determine the implementation of academic supervision and teacher performance assessment, through programs, implementation and evaluation of academic supervision planning and teacher performance assessment. This study uses a qualitative approach with a descriptive method. Data collection techniques were carried out through interviews, observation. The research subjects were the principal, vice principal and teachers at SMA Negeri 3 Timang Gajah Bener Meriah. The data analysis technique used is descriptive qualitative analysis, while the data processing steps are data reduction, data display, and conclusions and data verification. The results of the study found that: (1) the academic supervision program and teacher performance assessment referred to the identification of problems faced by teachers based on the results of the previous year's supervision such as assessment, coaching, and helping teachers with difficulties; (2) the implementation of academic supervision and teacher performance assessment by the principal is carried out in three stages, namely: an initial survey before conducting academic supervision, class visits to find out the course of learning, and reviewing the results of class visits and providing appropriate solutions in overcoming problems faced by students. teacher; (3) evaluation and follow-up on the implementation of academic supervision and teacher work assessments carried out by school principals, including evaluation of job descriptions and evaluation of document evidence, by looking directly at evidence of tasks carried out by teachers and then principals providing input if there are errors or lack.@font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-536870145 1107305727 0 0 415 0;}@font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-520082689 -1073697537 9 0 511 0;}@font-face {font-family:Georgia; panose-1:2 4 5 2 5 4 5 2 3 3; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:647 0 0 0 159 0;}p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri",sans-serif; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-ansi-language:IN; mso-fareast-language:IN;}.MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:11.0pt; mso-ansi-font-size:11.0pt; mso-bidi-font-size:11.0pt; font-family:"Calibri",sans-serif; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-ansi-language:IN; mso-fareast-language:IN;}.MsoPapDefault {mso-style-type:export-only; margin-bottom:10.0pt; line-height:115%;}div.WordSection1 {page:WordSection1;}